Making dyslexia work for you - Goodwin, Vicki; Thomson, Bonita (London : Routledge, 2012)
A guide to overcoming the day-to-day difficulties associated with dyslexia. --from publisher description.
Finding out about dyslexia and the brain -- Exploring your dyslexia -- How dyslexia affects you -- Support from those close to you -- Reading the world of print -- Getting down what you want to say -- Getting done what you want to do -- Self-esteem and motivation -- Handling numbers -- Making memory work for you -- Helping yourself with technology -- Looking wider.
Includes index.
Includes bibliographical references and index.
Keywords: Dyslexics -- Education; Dyslexia; Study skills; Dyslexia; Dyslexics -- Education; Study skills; Popular works